Justification of ways increasing the immunity of special purpose radio communications - Shyshatskyi, Andrii; Hasan, Vitalii; Kryvenko, Mykola; Petrov, Oleksandr; Kravchuk, Serhii; Shidlovsky, Yuriy; Opalak, Andrii; Modlinskyi, Oleksandr; Kobylynskyi, Oleksii; Bezstrochnyi , Ihor (Technology audit and production reserves, 2021)
The object of research is the military radio communication system. One of the most problematic areas in the military radio resources management is the interference of military radio systems and facilities. A number of works have been devoted to the study of ways to increase the noise immunity of military radio communication systems and facilities. However, the known works contain some research results by scientists, which are aimed at increasing the noise immunity of military radio communication systems and devices and do not have a comprehensive approach. This work solves the problem of substantiating ways to increase the noise immunity of military radio communication systems and facilities. The scientific problem is solved by substantiating the methodological principles of increasing the noise immunity of military radio communication systems in conditions of a priori uncertainty. During the research, the authors used the main provisions of the queuing theory, the theory of automation, the theory of complex technical systems, as well as general scientific methods of cognition, namely analysis and synthesis. The novelty is that in the course of work: – the purpose of functioning of the noise protection system of military radio communication systems is formulated; – indicators and criteria for increasing the noise immunity of military radio communication systems have been determined; – decomposition of the solution of this problem into problems depending on the signal and noise situation is carried out. An approach based on the hierarchical decomposition of the networks functional structure, the behavior of which is described by stochastic differential (or difference) equations of the high dimension state, into a number of interconnected but simpler functional structures is used for the functional description of military radio communication systems. The proposed approach to describe the behavior of military radio systems will allow to decompose the military radio system state and increase the efficiency of decision-making to adjust operating modes and parameters in real time. The results of the research should be used at the stage of parameters operational management and modes of the system operation.